PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PERKEBUNAN (STUDI PADA PT. DPN II UNIT SEI KUANTAN-KUANSING) - Aprima Ilham; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at PT. DPN II Unit Sei Kuantan Kuansing with a problem in this research is the low employee performance. The purpose of this study is to determine and analyze the effect of compensation and work discipline on employee performance partially and simultaneously. This study uses a questionnaire as a data collection tool that is distributed to 84 respondents to employees of PT. DPN II Unit Sei Kuantan Kuansing. The data is then processed using descriptive analysis and quantitative analysis using SPSS by conducting validity, reliability testing, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2) and hypothesis testing with t (partial) and F (simultaneous) testing. The results showed that the first hypothesis testing which is compensation for employee performance, namely tcount (8,118)> ttable (1.989), meaning that compensation has a significant effect on employee performance. second work discipline on employee performance is tcount (9.836)> ttable (1.989), meaning that work discipline has a significant effect on employee performance. The results of the test Fcount (60.838)> Ftable (3.11) means that compensation and work discipline have a significant effect on employee performance.Keywords: Compensation, Work Discipline, Employee Performance